Website-Based Boarding House Rental Information System: Case Study at Pondok Saluyu Company - Muharam, Andika Saputra; Solihin, Solihin; Retnaldi, Eko; Rahmawati, Eti; Emalia, Lilis (Journal of Economics, Management, and Entrepreneurship, 2024)
A traditional information management system is still in use at Pondok Saluyu, a boarding house in Bandung City. This method is unsuccessful or inefficient, particularly regarding marketing and providing potential tenants with information. This project aims to create and implement a web-based information system to facilitate digital payments, streamline the online room rental procedure, and distribute information more efficiently. Agile development, which enables quick development, adapts to change, and actively incorporates all relevant parties in the process, is the system development methodology employed. The findings of this study should make it easier for boarding house operators to verify room availability, manage boarding rooms, and handle tenant transactions. Additionally, this website will serve as a more contemporary form of advertising. The use of mobile/Android applications for system optimization, payment gateways to enhance payment systems, the creation of more comprehensive applications, and the improvement and development of programs in line with technological advancements are some recommendations for future development.